Midline theta dissociates agentic extraversion and anhedonic depression. (June 2015) - Mueller, Erik M.; Panitz, Christian; Pizzagalli, Diego A.; Hermann, Christiane; Wacker, Jan
Highlights: Study of anhedonia–agency relations using EEG in depressed and healthy subjects. Questionnaire measures of anhedonia and agency show high correlations. Anhedonia but not agency relates to altered theta response to positive feedback. Agency but not anhedonia relates to feedback-independent frontal vs. parietal theta. Agency and anhedonia are neurobiologically separable constructs. Abstract: The agency facet of extraversion is related to individual differences in reward anticipation and has been linked to the neurotransmitter dopamine. Dopamine has also been associated with components of anhedonia, which is one of the cardinal symptoms of depression and refers to lack of responsiveness to pleasurable stimuli. This raises the question whether low agency is associated with anhedonia symptoms in depression and if agency and anhedonia are characterized by similar neurobiological mechanisms. To address this hypothesis, we tested whether questionnaire measures of agency and anhedonia are correlated within depressed ( n  = 20) and non-depressed ( n  = 22) participants. Further, we investigated whether dopamine-related signatures in the EEG recorded during a gambling task (feedback-evoked theta activity, and frontal versus posterior theta activity) similarly relate to agency and anhedonia. Results indicated that anhedonia was significantly elevated in the depression group, and negatively correlated with agency. However, while theta activity evoked by negative vs. positive feedback was sensitive to anhedonia and depression status but unrelated to agency, frontal versus parietal theta activity predicted agency, but was unrelated to anhedonia and depression. Together, this double dissociation suggests that in spite of considerable phenotypical overlap, anhedonia and agency may be linked to partially distinct neurobiological markers.